CD8+ T cell response to human papillomavirus 16 E7 is able to predict survival outcome in oropharyngeal cancer. (November 2016) - Masterson, Liam; Lechner, Matt; Loewenbein, Sarah; Mohammed, Hassan; Davies-Husband, Cameron; Fenton, Tim; Sudhoff, Holger; Jani, Piyush; Goon, Peter; Sterling, Jane
Abstract: Introduction: Immunological response to human papillomavirus (HPV) in the development and progression of HPV16+ oropharyngeal squamous cell carcinoma (OPSCC) (accounting for the majority of viral associated cases) is largely unknown and may provide important insights for new therapeutic strategies. Methods: In this prospective clinical trial (UKCRN11945), we examined cell-mediated immune responses to HPV16 E2, E6 and E7 in peripheral blood using IFN-γ enzyme-linked immunosorbent spot assay. CD56 +, CD4 +, CD8 + and regulatory T cell frequencies were also discerned by flow cytometry. Fifty-one study participants with oropharyngeal carcinoma were recruited. Control subjects were those undergoing tonsillectomy for benign disease. All patients were treated with curative intent by radiotherapy ± chemotherapy. Disease-specific survival was investigated by multivariate analysis. Results: HPV16 DNA was detected in 41/51 of the OPSCC participants. T cell responses against HPV16 E6 or E7 peptides were detected in 33/51 evaluable patients, respectively and correlated with HPV status. Matched pre- and post-treatment T cell responses were available for 39/51 OPSCC cases. Within the whole cohort, elevated post-treatment CD8 + response to HPV16 E7 correlated with longer disease free survival (multivariate DFS p < 0.03). Within the HPV + OPSCC cohort, a significant increase in regulatory T cells (p < 0.02) was noted after treatment. Conclusions: This is the first study to provide survival data in OPSCC stratified by cell-mediated immune response to HPV16 peptides. Within the HPV16+ OPSCC cohort, enhanced immunoreactivity to antigen E7 was linked to improved survival. An increase in regulatory T cell frequencies after treatment may suggest that immunosuppression can contribute to a reduced HPV-specific cell-mediated response. Highlights: As yet, few studies have investigated the interaction between T-cell response and the HPV16 E6 or E7 oncoproteins presented in OPSCC. Our data would suggest an attenuated response by CD4 + /CD8 + T-cells to HPV16 peptides after completion of radical therapy. Specific factors affecting disease free survival include retained CD8 + response to HPV16 E7 [post-treatment], HPV16 + status and not smoking. Increased immunosuppressive influences after treatment [for the HPV16 + cohort] are supported by a concomitant rise in Treg frequencies. Further studies are required to explain the resistance of tumour targets to cytotoxic T cells and to find potential novel therapeutic strategies.